Dimethylammonium 4-hydroxybenzoate - Sornamurthy, B. M. (International Union of Crystallography, 2012)
In the crystal structure of the title compound, C(2)H(8)N(+)·C(7)H(5)O(3) (−), the anions and cations are linked by O—H⋯O and N—H⋯O hydrogen bonds into layers parallel to the ac plane.